'Farming is not Just an Occupation [but] a Whole Lifestyle': A Qualitative Examination of Lifestyle and Cultural Factors Affecting Mental Health Help‐Seeking in Australian Farmers. Issue 1 (15th October 2019) - Vayro, Caitlin; Brownlow, Charlotte; Ireland, Michael; March, Sonja
Abstract: The aim of this study was to understand the 'farming life' factors that affect the mental health help‐seeking of farmers. Semi‐structured interviews were completed with 10 farmers, 10 farmers' partners, and eight General Practitioners (GPs), covering mental health help‐seeking. Interview data were then analysed using thematic analysis resulting in three themes: Lifestyle and culture, farming priorities, and the challenges of farming. The findings showed that the lifestyle and culture of farming values traits such as stoicism and self‐reliance, which is ingrained in farmers' identities and appears antithetical to mental health help‐seeking. The farming priorities theme highlighted that farmers are time‐poor and believe mental health help‐seeking to be time‐consuming and an interference to their work, which is their primary priority. Lastly, this research revealed that farming challenges, such as financial volatility, increase the need for help, but can also reduce the ability to seek help. Implications of the findings highlight a need to carefully engage with farming cultures more broadly when seeking to support the mental health of the farming community.